2022
DOI: 10.1108/ajim-05-2021-0133
|View full text |Cite
|
Sign up to set email alerts
|

Competitive intelligence practices in Japanese companies: multicase studies

Abstract: PurposeThis study investigates competitive intelligence (CI)-related practices in companies, including process, scope and organizational structure. As these aspects have not been sufficiently discussed in the literature, the study objective is to determine (1) the type of CI process being employed, (2) whether the CI scope is limited to competitor analysis or spans a broader business environment and (3) whether the CI process and scope vary depending on organizational CI.Design/methodology/approachAn interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…There is no shortage of definitions of competitive intelligence. Essentially, this type of intelligence focuses on collecting and analyzing information on market conditions, government regulations, industry competitors, and new products to help organizations attain their goals (Nasri, 2012;Tsuchimoto and Kajikawa, 2022). A review of the relevant literature and several studies demonstrates that there are many definitions of competitive intelligence.…”
Section: Literature Review 21 Competitive Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…There is no shortage of definitions of competitive intelligence. Essentially, this type of intelligence focuses on collecting and analyzing information on market conditions, government regulations, industry competitors, and new products to help organizations attain their goals (Nasri, 2012;Tsuchimoto and Kajikawa, 2022). A review of the relevant literature and several studies demonstrates that there are many definitions of competitive intelligence.…”
Section: Literature Review 21 Competitive Intelligencementioning
confidence: 99%
“…Therefore, competitive intelligence has become a significant part of the environmental scanning process in organizations. However, literature demonstrated that there are many benefits for competitive intelligence in the organization, such as predicting changes in market condition, determining new or potential entrants to the market, and acquiring knowledge about new technologies, products, and processes that affect the organization's activities (Nasri, 2012;Tsuchimoto and Kajikawa, 2022). Therefore, many scholars call to formalize the competitive intelligence function within an organization to carry out the following tasks which reflect the competitive intelligence steps: "planning and direction, collection of data, analysis and dissemination" (Kahaner, 1998).…”
Section: Literature Review 21 Competitive Intelligencementioning
confidence: 99%